Updated cost-effectiveness analysis of palivizumab (Synagis) for the prophylaxis of respiratory syncytial virus in infant populations in the UK. (1st December 2020) - Narayan, Omendra; Bentley, Anthony; Mowbray, Katie; Hermansson, Monika; Pivonka, Dominic; Kemadjou, Eric Ngonga; Belsey, Jonathan
Abstract: Aims: Respiratory syncytial virus (RSV) is a common cause of respiratory infection in infants and severe infection can result in hospitalization. The passive immunization, palivizumab, is used as prophylaxis against RSV, however, use in the UK is restricted to populations at high risk of hospitalization. This study assesses the cost-effectiveness (CE) of palivizumab in premature infants with and without risk factors for hospitalization (congenital heart disease [CHD], bronchopulmonary dysplasia [BPD]). Methods: A decision tree model, based on earlier CE analyses, was updated using data derived from targeted literature reviews and advice gained from a Round Table meeting. All costs were updated to 2019 prices. One-way and probabilistic sensitivity analyses were performed to assess the degree of uncertainty surrounding the results. Results: Palivizumab is dominant (i.e. clinically superior and cost saving) when used in premature infants born ≤35 weeks gestational age (wGA) without CHD or BPD and aged <6 months at the start of the RSV season, infants aged <24 months with CHD and infants aged <24 months requiring treatment for BPD within the last 6 months. Limitations: One-way sensitivity analysis suggests that these results are highly sensitive to the efficacy of prophylaxis, number of doses, impact of long-term respiratory sequalae, rate of hospitalization and mortality due to RSV. A conservative approach has been taken toward long-term respiratory sequalae due to uncertainty around epidemiology and etiology and a lack of recent cost and utility data. Conclusions: Palivizumab prophylaxis is cost-effective in preventing severe RSV infection requiring hospital admission in a wider population than currently recommended in UK guidelines. Prophylaxis in premature infants born <29 wGA, 29–32 wGA and 33–35 wGA without CHD or BPD aged <6 months at the start of the RSV season is not funded under current guidance, however, prophylaxis has been demonstrated to be cost-effective in this analysis.